Some Considerations On The Problems Of Identity And Humanitarian Security - Мудраков, Віталій Вікторович; Поліщук, Олександр Сергійович (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2020)
Introduction. The analysis of identity in the context of attempt to define humanitarian security in the light of current events in Ukraine has been considered. The prism of analytics is the intersection of social science and philosophical knowledge. The authors diagnose contemporary Ukrainian identity as a state of «perpetual worldview and social wobble», – the state of identity embarrassment, and also focus on values as key factors of self-identification. The need for cultural narrative as a nurturing of the value of the own identity and «the own philosophy» is emphasized. From this position the general meaningful content of the humanitarian component of security and some main points of its conceptualization have been deduced: «picture of the future», «affirmation of the actual state», «feeling of being together», «monadic personality». With such ideological mediation, there are certain allusions to the speed and quality of Ukrainian identity assertion. The aim and the tasks are to outline the foundations of the formation of similar needs in the formation of identity that emerge from the humanitarian analytics of current actual and potential philosophical-worldview studies. Research methods. Ensuring the productivity of the conclusions comes not only from the successful selection of qualitative literature, but also from the predominantly used methodology in its analysis and analysis of the real state of affairs. The objective realities that have become the object of research on the one hand appear as a real, so to say, tangible material, on the other hand, – interpretations in the minds of others. However, in both cases, it is about the adequacy of reading, strict transfer into theory structuring mode, making conclusion and prediction of the aspects defined by the purpose – description of the current state of identity changes and characterization of potential dangers by the terminology of humanitarian security components. Such symbiosis indicates the interdisciplinary approach: social science and philosophical areas. Their interleaving is most effective for such topic in the light of the usage of hermeneutical and phenomenological methods. Discussion. The most general orientation in the conversation about identity must undoubtedly be on the origin of this concept. Thus, for the first time the concept of identity and its scientific development appeared in the works of E. Erickson and J. Turner. E. Erickson states that identity is a multilevel structure, which is formed by social factors in the development of cultural norms, social statuses and roles, etc., and thus represents certain reflection of a person’s internal solidarity with social ideals and standards. Beginning in the 1970-s, this term has been actively involved in the scientific circulation and become the object of socio-humanities study. In particular, S. Freud and J. Lacan paid considerable attention to the problems of identification. In social psychology, C. Cooley, G. Le Bon, G. Mead, and G. Tarde addressed this problem. According to the latter, identity is not only a social phenomenon but also a process. In this case, it is not so much about the concept of «identity» as it is about «identification», that is, the process in which a person interacts with society and as a result of it (interaction) assumes social roles in relation to one or another collective action of a social group. Such an instruction is of particular importance to our research, since it points to possible ways of reformatting identical constructions – the setting of qualitatively other projective tasks in the field of social-humanitarian policy by civic institutions. In addressing the definition of «with what?», actually, identity emerges under such conditions and in what terms to speak about it, the work of the well-known Lithuanian intellectual L. Donskins «Confused Identity and the Modern World» is published. A cross-section of the national-cultural definition of identity is offered by a collective monograph of Ukrainian philosophers, «National Identity and Civil Society», which has become perhaps the main reference point in understanding the particularities of national identity as a humanitarian security constant for this study. Conclusions. So, by healing oneself in the way of overcoming embarrassment and asserting own identity, a person becomes ready to be responsible for every act of his life-long progress as ultimately determining for his or her collective being, that is, for the whole people. In other words, being prepared to become a model is a way of forming belonging to the world of collective values and tolerant policy of recognition. Besides, it is also the imperative to preserve identity health. This, therefore, is a challenge for ourselves – the formation of the new European identity in Ukraine through the restoration of historical memory as the affirmation of the cultural narrative for the present and the future. This is, in fact, the first step in creating «own philosophy» – the culture of ideas and nurturing of self-esteem, not only as a theoretical principle, but also as a daily life-practical duty: world-view priorities, ways of thinking, results of value reformatting as a process of continuous improvement.Therefore, based on such guidelines and the real Ukrainian situation, it can be argued that humanitarian security in the aspect of forming collective identity is a certain balance of national-spiritual values with socio-political ones, this world-view health is embodied by intellectual taste, it is the awareness of the multiplicity of spiritual paths as political unity. This is the way which the modern Ukrainian is moving towards in the civilized world. It is, therefore, a question of democratic principles as a result of the self-development of society – from the social science standpoint, from a philosophical point of view – the possibility of the essential progress of the contemporary as the development of the capacity of own collective identity. Identity, therefore, allows one to have history or fully produce a historical narrative, claiming own exclusive rights as a narrator, who connects the past with the future, thus conveying and reinforcing the tradition. Thus, identity serves as a passport to the self-legitimization of a cultural narrative, for which there is no concept of fate in the modern world, it must enable itself and secure itself through its self-awareness.